2015
DOI: 10.15537/smj.2015.2.10304
|View full text |Cite
|
Sign up to set email alerts
|

Euthyroid sick syndrome in children with diabetic ketoacidosis

Abstract: Objectives:To investigate characteristics of euthyroid sick syndrome (ESS) in children with diabetic ketoacidosis (DKA).Methods:This retrospective study was carried out between May 2010 and April 2013 at the Pediatric Department of Shandong Provincial Hospital, Shandong University, Shandong, China. Diabetic ketoacidosis children were divided into 2 groups: euthyroidism (group one, n=30) and ESS (group 2, n=40). C-peptide, glycosylated hemoglobin (HbA1c), bicarbonate, anion gap (AG), free triiodothyronine (FT3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
23
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 13 publications
7
23
0
2
Order By: Relevance
“…The exact underlying causes have not yet been clari ed although many hypothesis have been proposed [12,18,23,24]. In previous research, FT3 and FT4 levels were positively correlated with bicarbonate levels and negatively correlated with HbA1c and AG levels [13]. In the present study, we evaluated the role of more parameters including acute phase reactants and metabolic parameters in the speci c situation.…”
Section: Discussionmentioning
confidence: 85%
“…The exact underlying causes have not yet been clari ed although many hypothesis have been proposed [12,18,23,24]. In previous research, FT3 and FT4 levels were positively correlated with bicarbonate levels and negatively correlated with HbA1c and AG levels [13]. In the present study, we evaluated the role of more parameters including acute phase reactants and metabolic parameters in the speci c situation.…”
Section: Discussionmentioning
confidence: 85%
“…This state is connected with acute or chronic disorders of various organs and systems and is characterized by total T3 and free triiodothyronine (FT3) concentrations below and thyroid-stimulating hormone (TSH) concentration within normal range. A previously conducted study in T1DM patients with diabetic ketoacidosis (DKA) was focused on demonstration of temporary and slight changes of total T3 [ 4 ]. Only a few studies were focused on thyroid function and microvascular complications of diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple factors may contribute to the development of ESS [11,15,16]. In previous research, FT3 and FT4 levels were positively correlated with bicarbonate levels and negatively correlated with HbA1c and AG levels [7]. In the present study, we apprised more number of parameters including some acute phase reactants and nutritional markers in addition to metabolic parameters.…”
Section: Discussionmentioning
confidence: 83%
“…A study by Hu et al showed that children with T1DM diagnosed with DKA and were found to have ESS had a higher level of HbA1c, anion gap, and plasma glucose, whilst having a lower level of bicarbonate in comparison with those without ESS [7]. However, it was a retrospective case-control study, which is potentially susceptible to recall and selection bias.…”
mentioning
confidence: 99%
See 1 more Smart Citation